Vitamin D Receptor Deficiency Does Not Affect Blood Pressure and Heart Function - Grundmann, Sarah M.; Schutkowski, Alexandra; Schreier, Barbara; Rabe, Sindy; König, Bettina; Gekle, Michael; Stangl, Gabriele I. (Frontiers in Physiology, 2019)
Vitamin D is thought to play a role in blood pressure regulation, which in turn can influence cardiovascular risk. Several meta-analyses of cohort studies found low serum levels of 25 hydroxyvitamin D to be associated with increased blood pressure or increased cardiovascular morbidity and mortality in the general population. Active vitamin D mediates its function via the vitamin D receptor (Vdr), which is a ligand-activated transcription factor. A suitable model to examine the causal role of vitamin D in blood pressure regulation and heart function is the Vdr knockout (Vdr-/-) mouse. To elucidate the role of vitamin D on blood pressure, heart function, and cardiac myocyte size, we conducted a long-term study using Vdr-/- mice and well-defined diets. Group 1 comprised Vdr-/- mice that received a high-calcium, high-phosphorus rescue diet to prevent hypocalcemia and a rickets phenotype. Groups 2 and 3 included Vdr+/+ mice that were fed either the rescue diet or a control diet containing normal amounts of these minerals. As Vdr is a nuclear factor that regulates transcription, we analyzed the renal mRNA expression and serum concentration of renin and found that the Vdr-/- group had an almost 50% higher renin mRNA expression in the kidney compared to both groups of Vdr+/+ mice. Additionally, serum concentration of renin in Vdr-/- mice was significantly higher than that of Vdr+/+ mice that received the rescue or control diet (+17%, + 32%; P < 0.05). In contrast, renin activity was lower in Vdr-/- mice than in both groups of Vdr+/+ mice (P < 0.05). However, blood pressure, heart rate, cardiac myocyte sizes and the expression of renal renin receptor, hepatic angiotensinogen and angiotensin II receptor type 1 in kidney, liver and heart, did not differ between the three groups of mice. Additionally, data from transthoracic echocardiography did not indicate the role of Vdr on heart function, as the left ventricular ejection fraction, fractional shortening, and velocity of blood flow were comparable between the three groups. To conclude, the roles of Vdr and therefore most probably of vitamin D, in blood pressure regulation and heart function, were not confirmed by our findings.